Workplace Digitalization and HR Innovation in the Era of Industry 5.0 - Meria, Lista; Sunarjo, Richard Andre; Andayani, Dwi; Toh Hua, Chua (APTISI Transactions on Management (ATM), 2025)
This study investigates the impact of workplace digitalization on human resource (HR) innovation within the context of Industry 5.0. While Industry 4.0 empha- sized automation, Industry 5.0 highlights the synergy between advanced tech- nologies and human-centric practices. To analyze this relationship, a survey was conducted involving 150 HR professionals across multiple industries in Indonesia, focusing on the adoption of digital HR tools and innovative practices. The findings reveal that workplace digitalization has a positive and significant ef- fect on HR innovation (β = 0.52, p < 0.01), particularly in recruitment, digital training, and performance management. However, barriers such as employee resistance and cybersecurity risks negatively moderate this relationship. This re- search contributes to the literature by linking digital transformation to HR prac- tices in the Industry 5.0 era and offers practical implications for managers in improving organizational readiness through digital HR innovation.